OUTCOMES IN CLOSED REAMED INTERLOCKING NAIL IN FRACTURES OF SHAFT OF FEMUR - Mohammad, Taj; Sawati, Alamzeb; Ahmed, Ashfaq; Awan, Abdus Saboor; Siddique, Siddique (Journal of Ayub Medical College Abbottabad, 2015)
Background: Femoral shaft fracture is one of the common fractures seen in accident and emergency department of our hospital. Violent forces are required to break this and strongest of human bones. There are various treatment modalities for femoral shaft fractures in adults like traction, brace, platting, intramedullary nail (IMN), external fixators and inter locking nails. The study was done with an objective to evaluate the results of closed reamed interlocking nail in fractures of shaft of femur. Methods: A prospective study of 114 cases of femoral shaft fractures was carried out at orthopaedic unit of Ayub Teaching Hospital Abbottabad during 1 year. All these cases were treated with statically locked nails under spinal or general anaesthesia. These cases were followed up for up to one year and Results of the interlocking nail were observed in terms of union and complications. Results: Out of 114 patients, 95 underwent union in 90-150 days with a mean of 110.68 days. Ten patients had dynamization within six weeks because of obvious fracture gap in radiograph. There were 3 patients who had non-union, and 6 patients had delayed union which was treated with dynamization. Conclusion: Close reamed interlocking intramedullary nail in femoral shaft fractures is the treatment of choice. Patient rehabilitation is early, hospitalization is short, and fracture healing response is good.